Ubiquitin Ligases in Cancer Immunotherapy – Balancing Antitumor and Autoimmunity. Issue 5 (May 2019) - Fujita, Yu; Tinoco, Roberto; Li, Yan; Senft, Daniela; Ronai, Ze'ev A.
Abstract : Considerable progress has been made in understanding the contribution of E3 ubiquitin ligases to health and disease, including the pathogenesis of immunological disorders. Ubiquitin ligases exert exquisite spatial and temporal control over protein stability and function, and are thus crucial for the regulation of both innate and adaptive immunity. Given that immune responses can be both detrimental (autoimmunity) and beneficial (antitumor immunity), it is vital to understand how ubiquitin ligases maintain immunological homeostasis. Such knowledge could reveal novel mechanisms underlying immune regulation and identify new therapeutic approaches to enhance antitumor immunity and safeguard against autoimmunity. Highlights: E3 ubiquitin ligases recognize their substrates in a spatial and temporal manner, requiring cell type-specific post-translational modifications that are often affected by the microenvironment (oxygen, nutrients, stress). E3 ubiquitin ligases are important negative regulators of T cell responses that restrain not only autoimmunity but also antitumor immunity. Targeting E3 ubiquitin ligases may be of therapeutic benefit in cancer immunotherapy, highlighting the need to comprehensively characterize E3 ligase expression and function in immune cells.